Preparation of Antimicrobial Compounds by Hydrolysis of Oleuropein from Green Olives - Walter, W. M. (1973)
Oleuropein, an intensely bitter glucoside, was isolated from green olives. Hydrolysis products obtained from oleuropein in sufficient quantity for further tests were: (i) β-3,4-dihydroxyphenylethyl alcohol prepared by acid hydrolysis of oleuropein; (ii) elenolic acid obtained by methanolysis of oleuropein, isolation of the intermediate acetal, and subsequent acid hydrolysis; and (iii) oleuropein aglycone formed by the action of β-glucosidase on the parent glucoside. Mass spectral verification of the isolated compounds and ultraviolet absorption data are given. Oleuropein and its aglycone had similar threshold levels for detection of bitterness, whereas elenolic acid and β-3,4-dihydroxyphenylethyl alcohol were not judged to be bitter.